Effects of cooling time, injection pressure, and material type on the mechanical properties of ballun insulator products in injection molding - Muhammad Rifqi Sepvian; Sugeng Hadi Susilo (Politeknik Negeri Lhokseumawe, 2026)
A major challenge in injection molding is the instability of mechanical properties in products due to suboptimal process parameter settings, which necessitates identifying the optimal parameter combination to achieve adequate tensile strength and hardness. This study aims to evaluate the effects of cooling time, injection pressure, and material type on the tensile strength and hardness of ballun insulator products produced by injection molding. Two thermoplastic materials, Polypropylene (PP) and High-Density Polyethylene (HDPE), were selected due to their different molecular structures and crystallization behavior, both of which influence mechanical performance. The materials were processed under varying cooling times (20, 25, 30, and 35 s) and injection pressures (24, 27, 30, 33, and 36 bar). The novelty of this study lies in the comparative evaluation of PP and HDPE under identical process conditions for ballun insulator applications. The results showed that higher injection pressure improved mold-filling and molecular chain compaction, leading to increased tensile strength, while longer cooling time promoted more controlled crystallization and improved surface hardness. PP exhibited higher tensile strength due to its stiffer molecular structure, achieving a maximum tensile strength of 0.031 MPa at 36 bars. In contrast, HDPE showed higher hardness due to its denser crystalline structure, reaching 69.75 HD at 35 s cooling time. These findings indicate that material-specific optimization of injection molding parameters is important for achieving consistent mechanical properties and dimensional stability in ballun insulator products.